„Dziecko nieszczęścia”. Życie i twórczość Ludwiki Leśniowskiej - Stachura-Lupa, Renata (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The paper presents the life and literary works of Ludwika Leśniowska, an educational activist who wrote for the people. The author reconstructs the biography of Leśniowska and presents the principles of her social-literary programme. Leśniowska was active in Galicia, mainly in Cracow and Myślenice (near Cracow). She cooperated with the press for the people, e.g.: „Dzwonek”, „Dziennik Literacki”, „Włościanin”, „Zagroda”, „Gwiazdka Cieszyńska”. In 1864, as the author and editor of „Nowiny na Świecie”, she was accused of supporting the January Uprising and subsequently imprisoned. In 1859, the writer published Historia polska dla ludu, zebrana w krótkości z małymi objaśnieniami geografii i żywotami niektórych świętych i bohaterów polskich (Short collected history of Poland for the people, with short notes on geography and biographies of selected Polish saints and heroes) and in later years, she published novels for the people and occasional brochures. Her social-literary programme contained, among others, postulates of social solidarity and cooperation above social divisions, expansion of education, improvement of living and housing conditions among the poorer social groups, social utilitarianism of individuals, multiplying the wealth of the country through work and evoking patriotic feelings in people. For Leśniowska, the organic idea and work and devotion for the sake of others were a moral and patriotic duty and she found justification for them in Christian ethics which were based on trust in God and love for other people.